Sex-specific competition differently regulates the response of the rhizosphere fungal community of Hippophae rhamnoides–A dioecious plant, under Mn stress - Lin, Yuhu; Fang, Ling; Chen, Hao; Sun, Xudong; He, Yunxiao; Duan, Baoli; Li, Rui; Cao, Chuntao; Chen, Juan (Frontiers in Microbiology, 2023)
In this study, we investigated the soil physicochemical parameters and responses of rhizospheric fungal communities of Hippophae rhamnoides to Mn stress under different sexual competition patterns. The results showed that competition significantly affects soil physicochemical properties, enzyme activity, and rhizosphere-associated fungal community structures. Under Mn stress, soils with intersexual competition had higher levels of N supply than those with the intrasexual competition. Moreover, fungal communities under intersexual interaction were more positive to Mn stress than intrasexual interaction. Under intrasexual competition, female plants had higher total phosphorus content, neutral phosphatase activity, and relative abundance of symbiotic fungi in soils to obtain phosphorus nutrients to alleviate Mn stress. In contrast, male plants had relatively stable fungal communities in soils. In the intersexual competition, rhizosphere fungal diversity and relative abundance of saprophytic fungi in male plants were significantly higher than in female plants under Mn stress. In addition, female plants showed greater plasticity in the response of rhizosphere microorganisms to their neighbors of different sexes. The microbial composition in soils of female plants varied more than male plants between intrasexual and intersexual competition. These results indicated that sex-specific competition and neighbor effects regulate the microbial community structure and function of dioecious plants under heavy metal stress, which might affect nutrient cycling and phytoremediation potential in heavy metal-contaminated soils.